Analisis Kebugaran Jasmani Siswa SMK Negeri 1 Bawen Program Kejuruan Agribisnis Pengolahan Hasil Pertanian - Fauzi, Ahmad (MAN Insan Cendekia Jambi, 2024)
Physical fitness is an important component that supports student achievement. To assess the level of physical fitness among students, this study was conducted using a descriptive quantitative method involving 89 students from SMK Negeri 1 Bawen in the Agribusiness Agricultural Product Processing program. The sample was selected using a purposive sampling technique, meaning that it was chosen based on specific considerations. The variables studied were a push-up test to assess arm muscle strength, a sit-up test to evaluate abdominal muscle strength, and the Harvard step test to measure endurance. Data was collected by directly assessing the research subjects, and the results were then analyzed using percentage calculations across five categories of physical fitness levels. The results of the study indicate that the students' physical fitness level was identified as adequate, meaning the students were in a condition that was fresh and energetic enough to improve their achievements at school, both in academic and non-academic areas. This also suggests that the students were in sufficient condition to carry out daily activities, although additional training intensity is still necessary to further improve their physical fitness.